Caracterização de fitas supercondutoras 2G HTS em regime de Flux flow - Barusco, Pedro (2017)
According to the power law, the exponential factor (N) describes the V-I curve rise during the superconductor transition to the normal state. Moreover, N is important for the evaluation of the existing forces in the pinning mechanisms. It is an essential input parameter for the simulations of a wide range of applications such as coils, Superconducting Fault Current Limiters (SFCL) and other cases where the power law applies. This work explores experimental techniques based on the transport method and Four Lead configuration to obtain the N behavior of Second Generation High Temperature Superconductor (2G HTS) tapes beyond the Flux Creep regime. Since the value of N is extremely sensitive to the HTS tape temperature, the attention was held for ways to minimize the tape temperature oscillation during V-I measurements. First, a special copper sample holder was designed for utilizing the four probes measurement without the need of any soldered terminals, avoiding local degradation. The holder was also intended to serve as a thermal anchor, improving heat exchange in order to guarantee thermal stability. In addition, a homemade fast current source was created to apply current pulses with low duty cycle in order to reduce the thermal losses due to the significant resistance near and above critical current (Ic) values. Also, a pre-amplifier circuit was developed for continuous monitoring of voltage rise in the samples during the current pulse. The exponential factor N characteristics were obtained from V-I measurements for four 2G tapes models from different companies in self-field and liquid nitrogen bath. At last, the explored experimental techniques were used for the construction of a dry cooling current lead.